Multicenter Proficiency Testing of Nucleic Acid Amplification Methods for the Detection of Enteroviruses - Van Vliet, Karin E. (American Society for Microbiology, 2001)
A multicenter study of molecular detection of enteroviruses was conducted using a proficiency panel. Of 70 data sets, 46 (66%) reported correct results for samples containing at least 1 50% infective dose per ml and for negative samples. Variation in performance between laboratories demonstrates the need for ongoing quality control.